Brain Informatics and Health International Conference, BIH 2016, Omaha, NE, USA, October 13-16, 2016 Proceedings - Ascoli, Giorgio A.; Hawrylycz, Michael; Ali, Hesham; Khazanchi, Deepak; Shi, Yong (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the refereed proceedings of the International Conference on Brain and Health Informatics, BHI 2016, held in Omaha, USA, in October 2016. The 37 revised full papers, including two workshop papers from BAI 2016, presented were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections on cognitive and computational foundations of brain science; investigations of human information processing systems; brain big data analytics, curation and management; new methodologies for brain and mental health; brain-inspired intelligence and computing; brain and artificial intelligence.